POWER AND TRUST: A MEDIATOR IN THE RELATIONSHIP BETWEEN PROCEDURAL JUSTICE AND TAX COMPLIANCE IN INDONESIA - Stilia, Lilian Yuniar; Riandoko, Riko; Kartiko, Nafis Dwi (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
This study analyses the connection between procedural justice, trust and power concerning tax compliance in Indonesia and investigates the mediating influence of trust and power tax authorities hold in this relationship. While various factors play a role in tax compliance behaviour in Indonesia, the country still struggles to achieve maximum compliance, falling short of international standards in terms of tax ratio. Only half of Indonesians have confidence in the tax system, and procedural justice is closely linked to power and trust. This study is groundbreaking as it is the first to investigate these three factors simultaneously in Indonesia. A quantitative approach was employed, with data gathered from 371 taxpayers and analyzed using the PLS-SEM method. The findings indicate that legitimate power and trust are positively associated with voluntary tax compliance and function as mediators between procedural justice and tax compliance. However, no correlation was found between procedural justice and tax compliance or between coercive power and tax compliance. To enhance taxpayer compliance in Indonesia, it is recommended to bolster trust in the tax authority and its jurisdictions. This study addresses a gap in the tax compliance literature. It enhances the theoretical framework, providing valuable practical insights for compliance improvement strategies, particularly for the Indonesian Directorate General of Taxes. The findings support developing more effective policies, improving tax education, and promoting transparency to strengthen public trust and compliance.